Transformational Leadership: The Case of Human Resources Bureau of a Public University - Mia Nurul Khotimah; Abubakar; Nani Hartini; Yayah Rahyasih; Asep Dikdik (Edukasi, 2025)
This study aims to analyze the implementation of transformational leadership by three generations of leaders in the Human Resources (HR) Bureau of Universitas Pendidikan Indonesia (UPI). Participants included three former and current Bureau Heads (2015-2016, 2020-2024, and 2024-2028) with diverse educational backgrounds and extensive experience in educational administration and human resource management. Data were collected through semi-structured interviews using a validated protocol of 20 open-ended questions based on Bass & Riggio's transformational leadership dimensions, along with document studies of policy documents, performance reports, and bureau meeting archives. Through a qualitative approach and ATLAS.ti software-assisted data analysis, this study identifies how transformational leadership strategies improve employee performance, work motivation, organizational innovation, and build a value and technology-based work culture. The main findings show that leaders can formulate a clear vision, provide individualized support, build an open communication system, and utilize technology to strengthen work effectiveness. Visualization of the code shows a close relationship between aspects such as employee empowerment, strengthening collaboration, career development, and the use of digital-based performance reporting systems. This research recommends the need for a structured competency development system, data-based performance measurement, and strengthening cross-team communication to sustainably improve transformational leadership effectiveness in a changing work environment.